Impact on Health care associated Infection rates by Continuous training of Nursing staff in our hospital. - Mani, Ratna; Rao, Ratna (International Journal of Infection Control, 2012)
Over one million people die each year from complications of Health care associated Infections (HAI) It also causes morbidity, increased health care cost for the patient. Though now there is lot of awareness about the HAI and its prevention ,there is no structured format of the same for sisters . We developed a course for the sisters to be trained on Infection control practices and implemented it. The baseline data of Infection control indices prior to training was compared with that of data collected post training. There was a remarkable decrease in the rates of HAI. We now conduct this training programme twice in a year and have seen a constant improvement in our HAI rates. So we could control our HAI rates by simple initiative like basic training skills for our Nurses .Such programmes and trainings are very effective and can be adapted by resource poor countries for bringing down their Health care associated Infection rates